2007
DOI: 10.1227/01.neu.0000249230.67118.3c
|View full text |Cite
|
Sign up to set email alerts
|

Management of Petrous Endostosis in Posterior Fossa Procedures for Trigeminal Neuralgia

Abstract: Petrous endostosis is an uncommon finding in posterior fossa procedures for TN (3.4%). However, it can obscure the region of neurovascular conflict, which is venous compression in these cases. We have found that drilling away endostosis or using endoscopic-assisted microsurgery increases the chances of good outcome and avoids unnecessary rhizotomy. All magnetic resonance imaging scans should be inspected for evidence of petrous endostosis and, when present, a bone window computed tomographic scan should be per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Interestingly, the rate of negative exploration is quite variable, 18-28.5% depending on the experience of the surgeon. [36] In the retrospective cohort study of MVD by Kalkanis and colleagues the morbidity rates were signiÞ cantly lower at high-volume hospitals and with high-volume surgeons. The mortality rate was 0.3%, and the rate of discharge other than to home was 3.8%.…”
Section: Reasons For Recurrences Due To Mvdmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, the rate of negative exploration is quite variable, 18-28.5% depending on the experience of the surgeon. [36] In the retrospective cohort study of MVD by Kalkanis and colleagues the morbidity rates were signiÞ cantly lower at high-volume hospitals and with high-volume surgeons. The mortality rate was 0.3%, and the rate of discharge other than to home was 3.8%.…”
Section: Reasons For Recurrences Due To Mvdmentioning
confidence: 97%
“…[36] Thereafter, Barker et al, emphasized MVD by demonstrating a 70% cure rate in a 10-year follow-up study. [9] However, direct comparisons between various series are hindered by different deÞ nitions of operative success regarding the recurrence rate of tic pain after MVD that was done using actuarial methods.…”
Section: Microvascular Decompressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drilling of suprameatal tubercle give access to Meckel's cave and posterior part of middle cranial fossa [ 13 ]. However, drilling of supameatal tubercle maybe necessary in cases of microvascular decompression of trigeminal nerve if heavily calcified and enlarged tubercle encountered to expose the entire length of trigeminal nerve, especially when the offending vessel is not visualized under the enlarged tubercle [ [14] , [15] , [16] ]. Inoue et al reported EST in 48 (10.4%) of 461 patients treated by microvascular decompression for TN and 8 patients had resection of the enlarged tubercle (7 operated via retrosigmoid approach and 1 via anterior transpetrosal approach).…”
Section: Discussionmentioning
confidence: 99%
“…2 In such cases, the removal of the enlarged SMT may improve the surgeon's visualization of the NVC site. [3][4][5][6][7][8][9][10] SMT removal, however, is a technically demanding procedure, which requires meticulous maneuvers and experience, due to the potential risk of injuring the surrounding neurovasculature and cerebrospinal fluid (CSF) leakage. [3][4][5][6][7][8][9][11][12][13] Of 197 consecutive patients who underwent MVD at our institute over 7 years (2011)(2012)(2013)(2014)(2015)(2016)(2017), 20 required SMTremoval to complete the MVD.…”
Section: Introductionmentioning
confidence: 99%